Litigation in ophthalmology: An overview. (December 2019) - McMaster, David; Tucker, Charlotte
Through a series of Freedom of Information requests to NHS Resolution on claims made from 2005/2006 to 2017/2018 we have analysed trends of UK litigation in ophthalmology, identifying the most common causes and primary injuries for closed (settled) claims resulting in payment of damages during this 13-year period. We assess the most common causes of litigation in ophthalmology with respect to previous rulings in clinical negligence and provide a case example for discussion.